Unraveling Cardiovascular Risk in Renal Patients: A New Take on Old Tale - Provenzano, Michele; Coppolino, Giuseppe; De Nicola, Luca; Serra, Raffaele; Garofalo, Carlo; Andreucci, Michele; Bolignano, Davide (Frontiers in Cell and Developmental Biology, 2019)
Chronic Kidney Disease (CKD), defined with the presence of two main kidney measures, an estimated glomerular filtration rate <60 ml/min/1.73m2 and/or an increase in urine protein excretion (i.e. albuminuria), is an important public health problem. Prevalence and incidence of CKD have risen by 87 and 89%, worldwide, over the last three decades. The onset of either albuminuria and eGFR reduction has found to predict higher cardiovascular (CV) risk, being this association strong, independent from traditional CV risk factors and reproducible across different setting of patients. Indeed, this relationship is present in high risk cohorts of CKD patients under regular nephrology care, those suffering from hypertension or type II diabetes, but also in general, otherwise healthy population. As underlying mechanisms of damage, it has hypothesized and partially proved that eGFR reduction and albuminuria can directly promote endothelial dysfunction, accelerate atherosclerosis and the deleterious effects of hypertension. Moreover, the predictive accuracy of risk prediction models was consistently improved when kidney measures (eGFR and albuminuria) have been added to the traditional CV risk factors (i.e. Framingham risk score). These important findings led to consider CKD as an equivalent CV risk. Although it is hard to accept this definition in absence of additional reports, great efforts have been made to reduce the CV risk in CKD patients. A large number of clinical trials have been started testing the effect of drugs on CV risk reduction. The targets used in these trials were different, including blood pressure, lipids, albuminuria, inflammation, glucose. All these trials have determined an overall better control of CV risk, performed by clinicians. However, a non-negligible residual risk is still present depending from 1) a consistent portion of patients do not respond to study treatment, 2) the role of many CV risk factors in CKD patients has not been completely investigated yet. These combined observations provide a strong argument that kidney measures should be regularly included in individual prediction models for improving CV risk stratification. Further studies are needed to identify high risk patients and novel therapeutic targets in order to try to obtain a full CV protection in CKD patients.